2013
DOI: 10.1177/1066480713505053
|View full text |Cite
|
Sign up to set email alerts
|

Latina Women’s Experiences in a Stepfamily Education Course

Abstract: This study highlights the experiences of low-income Latina women who participated in a nationally recognized, research-based stepfamily education program. From a multicultural feminist framework, interviews were conducted with 13 Latina women living in stepfamilies. They were asked, using a semistructured protocol, about their experiences of taking the course with other stepfamilies, the best part of the course, and anything positive and negative that resulted from participation. Participants identified improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Detailed, research‐informed conceptual frameworks to guide best practices for stepfamily education exist (Adler‐Baeder, Robertson, & Schramm, ; Adler‐Baeder & Higginbotham, ), but those models and program designs need to be updated to better meet the needs of increasingly complex stepfamilies, based on variations in levels and type of structural complexity, as well as cultural and developmental contexts. Some information has emerged over the past decade, particularly in regard to meeting the needs of Latinx stepfamilies (e.g., Skogrand et al, , ); however, the field is open to innovation. The use of a social determinants of health lens, which recognizes the stigmas and constraints these families face, suggests prioritizing these resources in an effort to address health inequality and other evidence of inequity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed, research‐informed conceptual frameworks to guide best practices for stepfamily education exist (Adler‐Baeder, Robertson, & Schramm, ; Adler‐Baeder & Higginbotham, ), but those models and program designs need to be updated to better meet the needs of increasingly complex stepfamilies, based on variations in levels and type of structural complexity, as well as cultural and developmental contexts. Some information has emerged over the past decade, particularly in regard to meeting the needs of Latinx stepfamilies (e.g., Skogrand et al, , ); however, the field is open to innovation. The use of a social determinants of health lens, which recognizes the stigmas and constraints these families face, suggests prioritizing these resources in an effort to address health inequality and other evidence of inequity.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned Utah‐based study used a Spanish translation of the Smart Steps program and reported efforts to recruit for and implement the program in ways that would be more sensitive to culture. The team used formative evaluation processes and qualitative interviews with Latinx participants and facilitators and offered best‐practice recommendations for work with Latin American stepfamilies (Reck et al, ; Skogrand et al, ; Skogrand, Mendez, & Higginbotham, ). We recognize the diversity within Latinx stepfamilies based on country of origin and immigration history, among other factors, but offer these recommendations broadly with that caveat noted.…”
Section: Moving the Stepfamily Education Field Forwardmentioning
confidence: 99%